2018
DOI: 10.2337/dc17-0976
|View full text |Cite|
|
Sign up to set email alerts
|

The National Diabetes Education Program at 20 Years: Lessons Learned and Plans for the Future

Abstract: The National Diabetes Education Program (NDEP) was established to translate findings from diabetes research studies into clinical and public health practice. Over 20 years, NDEP has built a program with partnership engagement that includes science-based resources for multiple population and stakeholder audiences. Throughout its history, NDEP has developed strategies and messages based on communication research and relied on established behavior change models from health education, communication, and social mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The YMCA also provided the DPP to Medicare beneficiaries with prediabetes in participating YMCAs nationwide (1,6), reducing medical spending and utilization, inpatient admissions, and emergency department visits. In 2010, the National DPP (NDPP) was authorized by Congress to build an infrastructure of community-based programs across the country (74), with new regulations expanding CMS coverage for Medicare beneficiaries in 2015 (91,125). As mandated and funded by Congress, the Indian Health Service implemented the Special Diabetes Program for Indians demonstration project, translating the DPP lifestyle intervention across rural, reservation, and urban American Indian/Alaska Native communities (62).…”
Section: Research Gaps and Implications Of Current Translation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The YMCA also provided the DPP to Medicare beneficiaries with prediabetes in participating YMCAs nationwide (1,6), reducing medical spending and utilization, inpatient admissions, and emergency department visits. In 2010, the National DPP (NDPP) was authorized by Congress to build an infrastructure of community-based programs across the country (74), with new regulations expanding CMS coverage for Medicare beneficiaries in 2015 (91,125). As mandated and funded by Congress, the Indian Health Service implemented the Special Diabetes Program for Indians demonstration project, translating the DPP lifestyle intervention across rural, reservation, and urban American Indian/Alaska Native communities (62).…”
Section: Research Gaps and Implications Of Current Translation Researchmentioning
confidence: 99%
“…Despite a level of broad success, the DPP has been translated less effectively in populations at risk for disparities (125). Recent findings from the NDPP found that non-Hispanic whites lose more weight than do Hispanics and non-Hispanic blacks; low-income participants lose less weight than do those from high-income communities.…”
Section: Research Gaps and Implications Of Current Translation Researchmentioning
confidence: 99%
“…Diabetes prevalence has increased over time not only in adults; in the last two decades, T2DM has become increasingly more frequent among youth worldwide, a trend that seems to be especially related to obesity . The highest prevalence has been observed in the United States, where T2DM represents 10% to 50% of new cases of diabetes among adolescents and over 50% among minority groups, including Latin and Hispanic youth. In contrast, in Europe, T2DM is considered a rare disease, accounting for only 2% of new diabetes cases among youth .…”
Section: Introductionmentioning
confidence: 99%
“…For long-term success, diabetes health education is critical. The National Diabetes Education Program (NDEP) was established to translate findings from diabetes research studies into clinical and public health practice [ 7 ]. To achieve this task, patients and providers work together in a long-term, ongoing process.…”
Section: Discussionmentioning
confidence: 99%